Estimasi Potensi Limpasan Permukaan Menggunakan Penginderaan Jauh dan Sistem Informasi Geografis di Daerah Aliran Sungai Serang - Pradana, Annisa Kusuma; , Dra. Alif Noor Anna, M.Si; , Agus Anggoro Sigit, S. Si, M. Sc (2016)
Land conversion of agricultural area into built up area causes the ouput of hydrological system of the watershed is changed. The built up area causes rainfall change into runoff quickly, so impact on flooding. Serang watershed is categorized in the first priority watershed management or very critical watershed according to the Development Plan during 2010-2014 of Ministry of Forestry. The downstream of Serang watershed is vulnerable to flooding such as Serang Hilir Sub-watershed, Nagung sub-watershed and Sidatan sub-watershed. This study aims to: 1) determine the accuracy of Landsat 8 to extract the parameters of run off, and 2) determine the runoff potential (C) and its spatial distribution in the Serang watershed. The method used in the research is survey method. The survey was conducted to test the interpretation of land use using Landsat 8. Sampling done by stratified sampling method. The smallest unit of analysis is sub-watershed. Analysis method using spatial analysis with quantitative hierarchical approach using Geographic Information System software. Landsat 8 is used to extract the parameters of land use in the Serang watershed have a level of accuracy of 87.88%. The accuracy ≥85%, it means the precision level included in good category, so the data still can be used for further research. Serang watershed has a high potential runoff (the value of C equal to 66,07%). The value of C from analysis results for 6 years (2006-2011) amounted to 62.16%. The accuracy ≥85%, it means the precision level included in good category. Runoff coefficient (C) of Serang watershed which consists of six subwatersheds ranged from 51% to 75%. The largest run off potential located in the Ngrancah sub-watershed, the value of C equal to 75.92%, while the lowest value was in Serang Hilir sub-watershed, the value of C equal to 55.88%. Run off potential in Ngrancah sub-watershed influenced by slope, while in Serang Hilir sub-watershed influenced by land cover. Keywords: Run off Potential, Run off Coefficient (C), Watershed